PEMBINAAN PEMBACAAN AYAT AL-QUR’AN MELALUI PENGADAAN BUKU TAJWID PRAKTIS - Abdul Bari; Matnin Matnin (Jurnal Ngejha, 2021)
Education is a measure of a country's progress, the higher the education of a country's people, the higher the country's development will be. The high level of education will not only have an impact on one sector, but will have an impact on several sectors including the economic sector, per capita society, technology, public health and people's thinking. The recitation of the Koran must be read according to the Tajweed rules. Tajweed is an inseparable part of reading and writing the Koran (BTQ), because tajwid lessons contribute to students to read the Koran well and tartil, therefore to make it easier for students to read the Koran according to the rules / tajwid, with tajwid will help students to better understand the Koran properly and correctly. Then from there we chose a strategy for fostering the reading of Al-Quran verses through the provision of practical recitation books. In this study using Participatory Action Research (PAR) which includes planning for repetitive actions, namely planning, implementing, observing and reflecting planned.